Propuesta de un Plan de Manejo para el Venado de Cola Blanca en el Zoocriadero la Casa del Venado - Gavilánez Yánez, Oscar Daniel (2018)
The White-tailed Deer (Odocoileus virginianus ustus) is in danger of extinction since the indiscriminate hunting of this specie that has reduced its population in the Andes of Ecuador. For this reason, the objective of the research was to implement a management plan for the White-Tailed Deer in the Deer House- animal breeding, to control the parameters and improve the quality of life of this species in semi-captivity. This study starts from the evaluation of the characteristics of the deer house- animal breeding, which results will offer us an idea of how is its management. While, this research was carrying out, the behavior of white-tailed deer in semi-captive conditions was observed and parameters were established for the implementation of an optimal management plan for this species in "La Casa del Venado"- animal breeding. Some relevant data were obtained that served as a basis to search for sustainability and sustainable development of white-tailed deer (Odocoileus virginianus ustus) productions. In the country, we also seek to form reproductive processes, looking for the best phenotypic characteristics to establish new populations of this species in the Andes of the Sierra region in Ecuador. Finally, the breeding of white-tailed deer in semi-captivity simulating their natural environment and avoiding contact with humans as much as possible, can establish rebreeding processes among members of this species, observing their best physical and genetic characteristics for helping to the increase of this animal population in the Ecuadorian Andes.